Coupling Family Business Research with Organization Studies: Interpretations, Issues and Insights. Issue 6 (June 2019) - Salvato, Carlo; Chirico, Francesco; Melin, Leif; Seidl, David
Family-controlled firms are the most widespread form of business organization, but they have so far attracted limited attention from organizational scholars. The present work suggests that coupling research on family business organizations with organization studies will substantially benefit both areas of scholarly research. We explore how the five core defining features of family firms – ownership, management and governance, transgenerational intention, generational involvement and perceived identity – may be illuminated by extant research in organization studies, and how, in turn, organizational studies may be extended by investigating its key themes in the empirical context of family firms.